Validity and reliability of sensor system to measure trunk range of motion during Streamlined Wolf Motor Function Test in chronic stroke and aged-matched healthy participants. Issue 4 (19th May 2023) - Alhwoaimel, Norah; Warner, Martin B.; Hughes, Ann-Marie; Busselli, Giulia; Turk, Ruth
ABSTRACT: Objective: To investigate the validity and reliability of using the Valedo® system to measure trunk Range of Motion (ROM) during performance of the streamlined Wolf Motor Function Test (SWMFT). Methods: Twenty chronic strokes and 20 age-matched healthy participants performed SWMFT while wearing Valedo® sensors on their trunks to capture trunk movements. A paired sample T-test was used to examine the validity of the system in distinguishing between the healthy and stroke group, and between the affected and unaffected sides in the stroke group. Interclass correlation coefficients were used to assess the inter-rater and intra-rater reliability (between-days) with 95% CI. Results: The Valedo® system was able to distinguish between stroke and healthy participants; stroke participants employed greater trunk range of movements than the healthy controls in all tasks (p < .01). Furthermore, the Valedo® system enabled differentiation between affected and unaffected hands of people within the stroke group. The reliability for the stroke group was good to excellent with intrarater reliability (ICC = 0.71–0.92) and interrater reliability (ICC = 0.63–0.95). Conclusions: The Valedo system demonstrates an acceptable level of validity and reliability for measuring trunk ROM during the Streamlined Wolf Motor Function Test (SWMFT). Future studies with a larger sample size, different levels of upper limb impairment are warranted.